Casa de mani, mani oca, se tem farinha... De lá vem muito mais! Habitus, linguagem e memória: Um estudo interpretativo dos processos simbólicos no beneficiamento da mandioca - Miranda Filho, René Gouveia (2009)
Living is a long-known world of the past exchanged in this that is not lost when something is motivated in memory. The word remember is the link finding "under the baton of knowledge which grasps the world. In the experience of scientific speack is faced with the "simplicity", that complex word to refer to it cannot fail to imagine an act, a doing, a praxis or a building. To discuss the subject researched speech is a fact "imagined" in reality. Object, objetuação, targeting is said in done thing done. The house is part of flour not live off of, and there is the nature of the tuber in processed food in poéisis intensified in the hope of all hope done. The everyday world, world pass, circumvented the folds of word the naked want possible. The words given here reflect the gestures, the body, the senses of affection moved in time, spiral and anachronistic, time of existence represented among the ‘virtual’ and ‘real’. In search of scientific we move to try to decipher the enigmas of reality, and what you do is nothing more than try methodological rigor in shaping the world to externalize the perceptions on the empirical sensations volatilized in outsourced objects. Each grain of flour, formed the intense heat of the furnace, was substancializado of those who do shave, Cerro, wash, press and roasting the mass of cassava. Many have departed and the other no longer made in the memory of life, pleasant, meanings. Your José Jorge, well done, leave the memories his knowledge of world. Want to know the ‘Other’ is a time to know each other, even the intimacy of thinking, steeped in the vast intersubjectivity. The said was "done" in reality the inset, onset of symbolic forms that the words. The house of flour Site II was neither monkey scene and not stage, but ‘the background’ of a ritual performed in mitopraxis aesthetics of a living thought. In an ethnographic, study that aims, proposes to strip the living, intentionally thought, therefore something exists only because a meaning is inferred. The product of cassava processed into flour, gum, beiju, carim is there as an object ‘real’, ‘touch’ and ‘enjoyable’ and also ‘symbolized’. In culture of imagination, the plant that hides its fruit on earth, substantiating a wisdom imaginary in songs, words spoken, cordage, chanson, meizinhas, fruit spirits of poets and sing live for the people of the Hinterland caatingas, the feet of mountains and near the sea. That said this study invites all to know a little of the world's cassava done things that nourish our bodies and minds.